What this comedian said will shock you eaudiobook - Maher, Bill (Simon & Schuster Audio, 2024)
The hilarious and controversial host of HBO's Real Time with Bill Maher has written his funniest, most opinionated, and most necessary book ever—a brilliantly astute and acerbically funny vivisection of American life, politics, and culture. Some of the smartest commentary about what's happening in America is coming from a comedian—this comedian being Bill Maher. If you want to understand what's wrong with this country, it turns out that one of the best informed and most thought-provoking analysts is this very funny pothead. The book was inspired by the "editorial" Bill delivers at the end of each episode of Real Time . These editorials are direct-to-camera sermons about culture, politics, and what's happening in the world. To put this book together, Maher reviewed more than a decade of his editorials, rewriting, reimagining, and updating them, and adding new material to speak exactly to the moment we're in. Free speech, cops, drugs, race, religion, the generations, cancel culture, the parties, the media, show biz, romance, health—Maher covers it all. The result is a hugely entertaining work of commentary about American culture in the tradition of Mark Twain, Will Rogers, and H. L. Mencken.